Granulomatous mastitis, erythema nodosum, and arthritis syndrome: a narrative review - Li, Sheng-Guang; Zhang, Jing; Li, Ji; Zhang, Lina; Zou, Yadan; Long, Ting; Yu, Ruohan; Zhang, Yanfeng (Frontiers in Immunology, 2025)
IntroductionIdiopathic granulomatous mastitis (IGM) is a rare chronic inflammatory breast disease of unknown etiology, typically presenting with breast pain, swelling, and mass formation. Erythema nodosum (EN) is an inflammatory panniculitis that can occur as a systemic manifestation of various conditions, and arthritis has occasionally been observed alongside granulomatous mastitis (GM), suggesting an underlying autoimmune component. This narrative review synthesizes reported cases of GM with EN, with or without arthritis—termed “GMENA” syndrome—to characterize its clinical features and management.MethodsWe searched PubMed and EMBASE for case reports and case series describing GM with co-occurring EN, with or without arthritis. Reports fulfilling these criteria were reviewed, and data on demographics, clinical presentation, laboratory and histological findings, treatment strategies, and outcomes were extracted and summarized descriptively.ResultsWe identified 45 reported patients with GMENA in the literature. All patients were women of reproductive age (median age approximately 32 years), and about one-third presented during pregnancy or in the postpartum period. Breast involvement was exclusively unilateral, manifesting as painful inflammatory masses often mimicking carcinoma. EN was universal (100%), usually affecting both shins and ankles, and approximately two-thirds of patients developed acute, non-erosive oligoarthritis, most commonly involving the ankles. Laboratory work-ups consistently showed elevated inflammatory markers with negative autoantibodies and sterile cultures. Histology typically revealed lobulocentric, non-caseating granulomas with neutrophilic microabscesses. Corticosteroids induced remission in more than 75% of cases, while methotrexate or azathioprine provided steroid-sparing benefit in refractory disease. Antibiotics and anti-tuberculous regimens were generally ineffective, and surgery was mainly used for biopsy, drainage, or limited excision. Relapses (about 13%) were uncommon and often followed rapid tapering of corticosteroids.DiscussionGMENA appears to represent a distinct clinicopathologic entity within the spectrum of IGM, characterized by the triad of granulomatous mastitis, EN, and frequently acute oligoarthritis in women of childbearing age. The available evidence supports an underlying immune-mediated mechanism and favors systemic corticosteroids, with early introduction of steroid-sparing immunosuppressants in refractory or relapsing disease. Antibiotics and extensive surgery have limited roles. Further prospective and mechanistic studies are needed to clarify pathogenesis and to optimize long-term management strategies.